A Quality Improvement Project in Balance and Vestibular Rehabilitation and Its Effect on Clinical Outcomes. Issue 2 (April 2016) - ALMohiza, Mohammad A.; Sparto, Patrick J.; Marchetti, Gregory F.; Delitto, Anthony; Furman, Joseph M.; Miller, Debora L.; Whitney, Susan L.
Abstract : Background and Purpose: Unwarranted variation in practice is among the principal contributors of suboptimal outcomes in health care. This variation can be minimized via quality improvement initiatives. However, quality improvement projects focus mostly on assessing processes, and less attention is given to the effect of the variation on clinical outcomes. An effective implementation of a clinical treatment algorithm (CTA) could improve care for individuals with balance and vestibular disorders. The first aim of this quality improvement project was to examine adherence to a CTA developed by physical therapists who treat persons with balance and vestibular disorders. The second aim was to examine the effect of adherence on patient outcomes. Methods: Twenty-three physical therapists who provided rehabilitation for individuals with balance and vestibular disorders participated in the quality improvement project. All physical therapists worked for the same health care provider, and developed the minimum data set and CTA. The physical therapists were cluster randomized into 2 groups; both groups received educational training and reminders regarding adherence to the CTA. The first group received the training and reminders after an 8-week baseline period (initial group), and the second group (delayed group) after a 12-week baseline period. The prescribed interventions were classified as being adherent or nonadherent to the CTA. Clinical outcomes, including the Activities-Specific Balance Confidence (ABC) scale, Dizziness Handicap Inventory (DHI), and the Global Rating of Change (GRC), were recorded at the initial evaluation and discharge for 454 individual with balance or vestibular disorders. Results: Across the 16-week project, adherence rates improved significantly by 9% and 12% for the initial and delayed groups, respectively ( P = 0.008), but there was no difference between groups related to the timing of the educational training and adherence reminders. Clinical outcomes improved for individuals, with balance or vestibular disorders but there was no differences in the change in ABC, DHI, and GRC scores based on whether the interventions were or were not adherent to the CTA. Discussion and Conclusions: This quality improvement project was effective in increasing the adherence to the CTA in both groups. Although on average individuals with balance and vestibular disorders showed improvement on the clinical outcomes, there was no additional benefit in the clinical outcome for adherent interventions. Video abstract is available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A125 ). Abstract : Supplemental Digital Content is Available in the Text.